Pyogranulomatous mural folliculitis in a cat treated with methimazole. Issue 6 (June 2014) - Castro López, Jorge; Lloret, Albert; Ravera, Ivan; Nadal, Aina; Ferrer, Lluís; Bardagí, Mar
An 11-year-old spayed female domestic shorthair cat was presented for polydipsia, hyperactivity and bilateral thyroid gland enlargement. Total T4 (TT4 ) was in the upper interval range; therefore, an early hyperthyroidism was suspected. A treatment trial with methimazole was started, as the owner refused further tests. Six months later the owner stopped the treatment. One year later, clinical signs persisted and TT4 was still in the upper interval range. Methimazole was re-introduced but 48 h later the cat presented non-pruritic alopecia with erythema, scales and perilesional yellowish crusts. Pyogranulomatous mural folliculitis was diagnosed by histopatological examination of the skin biopsies. Methimazole was withdrawn and macroscopic lesions healed and disappeared histologically in 15 days. An idiosyncratic drug reaction to methimazole was suspected. To the best of our knowledge, this is the first report of feline pyogranulomatous mural folliculitis likely secondary to an adverse drug reaction to methimazole administration.